Comparison of Nanotech Assisted PCR Diagnosis of Mycobacterium tuberculosis with Conventional Methods - Deepak Sawant; Shivaji Pawar; Rajendra Patil; Siddhi Sawant (Advanced Concepts in Pharmaceutical Research Vol. 9, 2024)
Aims: This study was focused on the assessment and performance of traditional TB diagnosis methods and new innovative nanotech-assisted TB methods. The main aim of this study is to undertake the use of magnetic nanoparticles for TB detection. Study Design: A total of 400 pulmonary sputum samples of suspected TB patients were selected for this study out of these 30% (120) were selected for comparative study. Cross-sectional studies were conducted on clinical and radiological suspected TB patients. Place and Duration of Study: A total of one hundred and twenty clinically suspected TB patients were selected from D Y Patil Medical College Hospital and Research Institute Kolhapur, for a cross-sectional study in the month of August 2016 to January 2017. Samples were processed for diagnosis of TB by ZN stain, culture on L.J. medium and real-time PCR tests. Methodology: Selection of patient. Inclusion criteria include clinically diagnosed and radiologically documented new cases of pulmonary Mycobacterium tuberculosis of any gender and age group or untreated MTB cases and patients with anti-tuberculosis drug therapy in the past 6 months. Exclusion criteria include patients with anti-TB therapy or its constituent drugs in the past 3 months. The control group was also studied from the patients who had diagnoses other than pulmonary tuberculosis. Results: In our present study, 60.83% (73) of patients were male and 39.17 % (47) were female patients, showing a borderline male prevalence found in our study. Eighteen percent of patients were found to be in the age group (21-30 years) and are mostly affected by pulmonary tuberculosis. MNPs method 99.66% was found to be significant (P < 0.0001**). Conclusion: In the present study the MNP-DNA extraction techniques with NALC followed by IS6110 target amplification were found superior for diagnosis of TB. The MNP-assisted extraction method showed better results.